Peran Negara dan Pendidikan dalam Membentuk Mentalitas Rakyat Demokratis: Kajian Psikologis dan Sosial - Anisa Karina Ardiani; Yudinda Ababiel Salsabila; Puspita Amalia Rani (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
This research analyzes the role of the state and education in shaping people's democratic mentality through psychological and social approaches. The research method used is descriptive qualitative, with data collection through interviews, observations, and literature studies of teachers, students, community leaders, and education bureaucrats. The results show that the state contributes through civic education policies, curriculum implementation, and character programs such as the Pancasila Student Profile. Educational institutions function as a vehicle for the formation of democratic attitudes through participatory and dialogic learning. Psychosocial factors such as parenting, social media and culture also influence the internalization of democratic values. The formation of a democratic mentality requires synergy between the state, education and society to create active, critical and inclusive citizens.